Synthesis, Optical Properties and Photovoltaic Application of the SnS Quasi-one-dimensional Nanostructures - Wang, M. X.; Yue, G. H.; Lin, Y. D.; Wen, X.; Peng, D.L; Geng, Z. R. (Nano-Micro Letters, 2013)
Low-toxicity single crystal SnS nanowires had been successfully synthesized by the catalyst-assistant chemical vapor deposition. Au nanoparticles were applied on the ITO surface as the catalysis, using SnS powder and S powder as forerunners. The structure, morphology and optical properties of the prepared SnS nanowires were characterized. The experimental results show the as-synthesized nanowires are single crystalline with a preferential orientation. The synthesized SnS nanowires show strong absorption in the visible and near-infrared spectral region, and the direct energy band gap of SnS nanowires is 1.46 eV.